4-Hydroxyphenylacetic Acid Prevents Acute APAP-Induced Liver Injury by Increasing Phase II and Antioxidant Enzymes in Mice - Zhao, Hongqiong; Jiang, Zhihui; Chang, Xuemei; Xue, Huiting; Yahefu, Wumaierjiang; Zhang, Xiaoying (Frontiers in Pharmacology, 2018)
Acetaminophen (APAP) overdose is the principal cause of drug-induced acute liver failure. 4-hydroxyphenylacetic acid (4-HPA), a major microbiota-derived metabolite of polyphenols, is involved in antioxidative action. This study seeks to investigate the ability of 4-HPA to protect against APAP-induced hepatotoxicity, as well as the putative mechanisms involved. Mice were treated with 4-HPA (6, 12, or 25 mg/kg) for three days, one hour after the last administration of 4-HPA, a single dose of APAP was intraperitoneally infused for mice. APAP caused a remarkable increase of oxidative stress markers, peroxynitrite formation, and fewer activated phase II enzymes. 4-HPA increased Nrf2 translocation to the nucleus and enhanced the activity of phase II and antioxidant enzymes, and could thereby ameliorate APAP-induced liver injury. Studies reveal that 4-HPA, as an active area of bioactive dietary constituents, could protect the liver against APAP-induced injury, implying that 4-HPA could be a new promising strategy and natural hepatoprotective drug.